Assessing economic impact of research and innovation originating from public research institutions and universities—case of Singapore PRIs - Sarah Cheah; Christopher Yu (Triple Helix, 2016)
Research and innovation activities from universities and public research institutes (PRIs) contribute to economic growth in significant ways. Given the hefty investment in R&D in both public and private sectors, it is essential for policy makers to have meaningful, relevant and practical metrics for measuring the impact of public-funded research and innovation. However, the definition of impact and its measurements seem to differ across the literature, making it difficult for scholars and policy makers to inform policy and direct future research. This paper aims to consolidate all parts of the proverbial elephants by reviewing the extant literature for university/PRI impact studies, analysing and synthesising the erstwhile disparate studies, discussing the current metrics and their issues and identifying gaps among the different research strands. Building on the endogenous growth theory and the Triple Helix, we contribute to the body of knowledge by offering a multi-level Impact Assessment Framework for assessing the economic impact of public research. In the context of the framework, we applied the transaction cost economics theory and net present value concept to propose a new indicator, realised imputed commercial value (RICV). We empirically establish that RICV is a better predictor than the traditional licensing revenue metric used by universities/PRIs of firms' propensity to repeat licensing agreement with them, thereby indicating academic innovation impact.
Keywords: 330; Commercialisation; Innovation impact; Net present value; Public R&D; Technology transfer